2021
DOI: 10.1039/d0sc04420b
|View full text |Cite
|
Sign up to set email alerts
|

Guest induced reversible on–off switching of elastic frustration in a 3D spin crossover coordination polymer with room temperature hysteretic behaviour

Abstract: Reversible switch between a robust bistable two-state room temperature spin crossover (SCO) and its transformation in a four-stepped elastically frustrated SCO due to guest inclusion in a metal–organic Hofmann framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…In another work by Real and co‐worker's, a 3D dual Hoffmann type CP viz. {Fe II (3,8phen)[Au(CN) 2 ] 2 }.xPhNO 2 ( 34 ) (3,8phen=3,8‐phenanthroline, PhNO 2 =nitrobenzene) was reported [110] . The authors show an interesting example wherein the dielectric environment of the pores played a critical role in distinguishing solvents, for instance, methanol from benzene derivative.…”
Section: Neutral N‐donor Linker‐based Mofs Displaying Molecular Recognition Via Different Signal Transduction Pathwaymentioning
confidence: 99%
“…In another work by Real and co‐worker's, a 3D dual Hoffmann type CP viz. {Fe II (3,8phen)[Au(CN) 2 ] 2 }.xPhNO 2 ( 34 ) (3,8phen=3,8‐phenanthroline, PhNO 2 =nitrobenzene) was reported [110] . The authors show an interesting example wherein the dielectric environment of the pores played a critical role in distinguishing solvents, for instance, methanol from benzene derivative.…”
Section: Neutral N‐donor Linker‐based Mofs Displaying Molecular Recognition Via Different Signal Transduction Pathwaymentioning
confidence: 99%
“…Sieklucka et al reported the Reproduced with permission. [89] Copyright 2021, Royal Society of Chemistry.…”
Section: Multiresponsive Sco Systemsmentioning
confidence: 99%
“…Indeed, azobenzene guests have been actively used in photo‐responsive materials such as dynamic cage and metal–organic frameworks (MOFs) [6, 49–51] . Secondly, as for the SCO host, the porous Hofmann‐type Fe II MOFs provide a promising platform, in which extraordinary SCO properties, diverse pore sizes and dynamic host–guest interactions have been well documented [52–56] . In addition, loading active guest into Hofmann‐type SCO MOF is proven to be a successful strategy toward active‐guest‐dependent SCO behaviors [57] .…”
Section: Introductionmentioning
confidence: 99%